2018
DOI: 10.1186/s13104-018-3687-9
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory pilot study on health education program to improve health literacy among female in their 20s

Abstract: ObjectiveHealth literacy (HL) is one of the most important concepts in women’s healthcare. The low cervical cancer screening rate for young Japanese women is an urgent issue. Cervical cancer is preventable, and cervical cancer screening behavior is associated with HL. Therefore, the present study aimed to elucidate the effects of a health education program to improve HL among young female undergraduate students in Japan. Immediately after completing the program, participants evaluated their level of satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A 2015 study of Mexican students’ knowledge of cervical and breast cancer used an educational strategy to increase clinical-focused cancer literacy; the results demonstrated a 21.2% increase in correct responses from pretest to posttest [ 20 ]. A 2018 study measuring health literacy in the context of cervical cancer screening in Japanese women found that an educational intervention increased health knowledge of the adult participants [ 21 ]. These studies point to the possibility of self-care improvements, including behavior changes that can lower cancer risk and increase how often patients seek care, alongside improved knowledge of a particular disease [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2015 study of Mexican students’ knowledge of cervical and breast cancer used an educational strategy to increase clinical-focused cancer literacy; the results demonstrated a 21.2% increase in correct responses from pretest to posttest [ 20 ]. A 2018 study measuring health literacy in the context of cervical cancer screening in Japanese women found that an educational intervention increased health knowledge of the adult participants [ 21 ]. These studies point to the possibility of self-care improvements, including behavior changes that can lower cancer risk and increase how often patients seek care, alongside improved knowledge of a particular disease [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 study measuring health literacy in the context of cervical cancer screening in Japanese women found that an educational intervention increased health knowledge of the adult participants [ 21 ]. These studies point to the possibility of self-care improvements, including behavior changes that can lower cancer risk and increase how often patients seek care, alongside improved knowledge of a particular disease [ 19 , 21 ]. The pilot intervention herein has similar potential.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review regarding HL and women's health suggested that readability, layout, and design were key components in developing effective printed materials [19]. We previously conducted a program development study, and all participants indicated high levels of satisfaction and understanding of the material, an appropriate level of difficulty of the curriculum, and had improved HL and knowledge of women's health after completing the program [15]. We sent e-mails (e.g., information about the menstrual cycle, gynecological diseases and women's health resources) to the participants' smartphone once a month for 3 months after the group lecture.…”
Section: Intervention Programmentioning
confidence: 99%
“…The inclusion criteria for both groups were: (ⅰ) female Japanese undergraduate students, (ⅱ) aged 20 years or older. The sample size for each group was set at ≥13 people based on the difference in HL scale scores in our previous study [15]. The study was conducted between March and October 2015.…”
Section: Participants and Settingmentioning
confidence: 99%
See 1 more Smart Citation